Degradation of iprodione by a novel strain Azospirillum sp. A1-3 isolated from Tibet - Pan, Hu; Zhu, Beike; Li, Jin; Zhou, Ziqiong; Bu, Wenbin; Dai, Yanna; Lu, Xiangyang; Liu, Huhu; Tian, Yun (Frontiers in Microbiology, 2023)
A bacterial strain A1-3 with iprodione-degrading capabilities was isolated from the soil for vegetable growing under greenhouses at Lhasa, Tibet. Based on phenotypic, phylogenetic, and genotypic data, strain A1-3 was considered to represent a novel species of genus Azospirillum. It was able to use iprodione as the sole source of carbon and energy for growth, 27.96 mg/L (50.80%) iprodione was reduced within 108 h at 25℃. During the degradation of iprodione by Azospirillum sp. A1-3, iprodione was firstly degraded to N-(3,5-dichlorophenyl)-2,4-dioxoimidazolidine, and then to (3,5-dichlorophenylurea) acetic acid. However, (3,5-dichlorophenylurea) acetic acid cannot be degraded to 3,5-dichloroaniline by Azospirillum sp. A1-3. A ipaH gene which has a highly similarity (98.72%-99.92%) with other previously reported ipaH genes, was presented in Azospirillum sp. A1-3. Azospirillum novel strain with the ability of iprodione degradation associated with nitrogen fixation has never been reported to date, and Azospirillum sp. A1-3 might be a promising candidate for application in the bioremediation of iprodione-contaminated environments.